2011
DOI: 10.1038/labinvest.2011.45
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan, a unique ARB, improves left ventricular remodeling of infarcted heart by activating PPAR gamma

Abstract: Unfavorable left ventricular (LV) remodeling after myocardial infarction (MI) leads to cardiac dysfunction. We examined whether Telmisartan, an angiotensin (Ang) II type I receptor blocker (ARB), could improve the recovery of LV function in a rat model of MI. The effect of Telmisartan as a peroxisome proliferator-activated receptor-g (PPAR-g) agonist was also investigated. After 28 days of MI, a significant improvement of survival was observed in the Telmisartan-treated rat group compared with the vehicle cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…Apart from effective BP lowering, telmisartan is also associated with renal protection, improved ventricular remodelling, reduced inflammation and oxidative stress, etc. [7][8][9][10]. Many authors have demonstrated the superiority of telmisartan when combined with other antihypertensives like amlodipine or HCT compared to monotherapy.…”
Section: Open Accessmentioning
confidence: 99%
“…Apart from effective BP lowering, telmisartan is also associated with renal protection, improved ventricular remodelling, reduced inflammation and oxidative stress, etc. [7][8][9][10]. Many authors have demonstrated the superiority of telmisartan when combined with other antihypertensives like amlodipine or HCT compared to monotherapy.…”
Section: Open Accessmentioning
confidence: 99%
“…1,2) Telmisartan, one of the angiotensin II receptor blockers (ARBs), is known to prevent cardiovascular events by reducing blood pressure 18) and to improve left ventricular remodeling induced by myocardial infarction (MI). 19) However, several patients have experienced side effects while taking telmisartan, including MI at a rate of 39/2036 (1.9%) and angina pectoris at a rate of 18/2036 (0.9%) (http://www.ehealthme.com/ drug/telmisartan/; accessed January 14, 2017).…”
mentioning
confidence: 99%
“…Other reports also showed that telmisartan was more effective in ameliorating coronary arterial remodeling and cardiac fibrosis and inflammation than losartan in a mouse model of obesity and type 2 diabetes and a rat model of myocardial infarction [23,24]. In addition to these studies, our previous report compared the effects of telmisartan with the same dose of ARBs including losartan [16].…”
Section: Discussionmentioning
confidence: 99%